2020
DOI: 10.1111/1467-8551.12450
|View full text |Cite
|
Sign up to set email alerts
|

Managing Job‐Related Diversity Processes in High‐Reliability Teams in the Emergency Department

Abstract: We examine how high-reliability teams (HRTs) manage job-related diversity, which refers to differences among team members in skills and experiences relevant to work tasks. Managing job-related diversity is important in HRTs because of the need for consistent performance in time-pressured situations with serious consequences for error. In a qualitative study, we observe and interview members of HRTs in a public hospital emergency department in Australia. Our findings reveal a set of six strategies that HRTs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Another interesting observation from the review has noted that researchers have primarily focused on quantitative studies. So far, only a single study has conducted a qualitative study in high-reliability teams to manage job-related diversity (Williams et al. , 2022).…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another interesting observation from the review has noted that researchers have primarily focused on quantitative studies. So far, only a single study has conducted a qualitative study in high-reliability teams to manage job-related diversity (Williams et al. , 2022).…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Out of these, 58 empirical studies applied survey methods to collect the data, and 29 studies used archival data from multiple sources, like the Dun and Bradstreet database and data of stock exchanges of different countries. It was interesting to report that quantitative studies have increased dynamically, but not a single study has applied experimental research, and only a single study has conducted a qualitative study (Williams et al, 2022) in JRD literature. The review has found that since 2011 there have been no conceptual studies published emphasizing JRD, which may contribute to the theoretical underpinnings, grounded theory, and theoretical framework.…”
Section: Applied Methodology and Methodological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the events, activities and interactions that happen in extreme contexts are multi-layered, high-stakes, fast-paced and unpredictable (Golden et al, 2018; Hällgren & Rouleau, 2019). Extreme contexts can often spring into periods of highly intense and swift action amid periods of more mundane activities at a slower pace (Geiger et al, 2021; Golden et al, 2018; Williams et al, 2022). When beginning to theorize such contexts, a researcher may be so overwhelmed by their context’s complexity and dynamism that they over-simplify extremeness by relating it only to concepts and theories they are already familiar with.…”
mentioning
confidence: 99%